KEDUDUKAN ANAK ANGKAT DALAM HUKUM ISLAM - Zulfan Efendi Hasibuan (Yurisprudentia: Jurnal Hukum Ekonomi, 2019)
Humans are created in pairs so they can have offspring, there are those who are descended from men and women, there are also those who are descended from men or women only, but there are also those who are not descendants. The desire to have offspring is a common thing for every human who has a family, sometimes the desire is not in line with expectations, so some parents will raise children to be cared for. Therefore it is necessary to trace how the status of adopted children and their position in the family.